PEMBERDAYAAN MASYARAKATDAN PEMASARAN OLAHAN HASIL ALAM DESA BENCOY - Muhammad Rangga Abdurrasyid; Muhammad Rifqi Abdul Jabbar; Neng Resti Wardani; Nunik Destria Arianti; Muhamad Muslih (Jurnal Abdi Nusa, 2021)
The village of bencoy has abundant agricultural potential or natural products so it is very good for improving the community's economy. Agricultural products or natural products owned by an area can be processed into various products, for example chips, rengginang, sale, cilok and so on. Empowerment activities and marketing of natural products are carried out by providing counseling and socialization to communities who have MSMEs and millennial youth farmer members with the aim of providing information and knowledge about processing natural products into various types of processed which are not only for their own enjoyment or consumption but also for family use. made into an effort that can improve the household economy and the village economy.